2016
DOI: 10.1080/01616412.2016.1147682
|View full text |Cite
|
Sign up to set email alerts
|

Restless leg syndrome: a risk factor of higher prevalence of anxiety and depression in Parkinson’s disease patients

Abstract: The presence of RLS in PD patients may increase the occurrence of both anxiety and depression, but the severity of the symptoms is not significant in the two groups of the PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, an association between pain and RLS in the PD patient population was not explored. 21 Further exploratory analysis by other studies dwell into the link between RLS and sleep disorders within PD without assessing pain. [22][23][24] An interesting investigation probed pain in PD within the context of depression and linked disability from pain with higher ratings on the Beck Depression inventory.…”
Section: Discussionmentioning
confidence: 99%
“…However, an association between pain and RLS in the PD patient population was not explored. 21 Further exploratory analysis by other studies dwell into the link between RLS and sleep disorders within PD without assessing pain. [22][23][24] An interesting investigation probed pain in PD within the context of depression and linked disability from pain with higher ratings on the Beck Depression inventory.…”
Section: Discussionmentioning
confidence: 99%
“…3 Attention deficit hyperactivity disorder, mood disorders, and other sleep disturbances are frequently comorbid with these conditions. [19][20][21][22] Both RLS and PLMS are associated with iron deficiency. [46][47][48][49][50] Most studies show that iron supplementation has been shown to improve symptoms, with goal ferritin levels > 50 µg/L, though no randomized clinical trials have been completed in children.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,18 Indeed, patients with RLS have significant comorbidities in the areas of attention deficit hyperactivity disorder (ADHD), mood disorders, migraine headaches, and other sleep disorders. [19][20][21][22] Periodic Limb Movements in Sleep Periodic leg movements are common in RLS. Periodic leg movements can occur during wakefulness or during sleep, known as periodic limb movements in sleep (PLMS).…”
mentioning
confidence: 99%
“…There are a variety of risk factors for patients with Parkinson's disease to develop depression. They include anxiety (91), premorbid history of depression (92), family history of depression (93), cognitive impairment (94), longer duration of illness (95), motor disability and gait as well as balance impairments (96), younger age (97), sleep disorders and restless leg syndrome (98), and female sex (99).…”
Section: Parkinson's Diseasementioning
confidence: 99%